Aptitudes À L’agriculture Des Eaux Souterraines Du Departement d’Agboville (Sud-Est De La Côte d’Ivoire) - Orou, Rodrigue Kotchi; Soro, Gbombélé; Soro, Drissa Tanina; Traoré, Abou; Fossou, Rosine Marie N’guessan; Soro, Nagnin (European Scientific Journal, ESJ, 2016)
In the department of Agboville, farmers are interested in the using of groundwater to improve the performance of their crops. But they didn’t know the effects of this water on the crops without. The main objective of this study is to determine the quality of groundwater to prevent the risk of soil alkalinization and salinization in the department of Agboville. Hydrochemical analysis of 28 wells used for irrigation of crops was carried out. The dry residue (RS), the osmotic pressure (π), Sodium Absorption Ratio (SAR), the percentage of sodium exchange (ESP), salinity potential (SP), and the coefficient or the Kelly ratio (RK) were determined. Wilcox diagram was also applied for this study. The results show that groundwater department are soft and lightly mineralized wiht a low salinity. 75% of samples from groundwater haves low salinity and 25% have an average salinity. The values of the Salinity Potential (SP <5), Kelly Ratio (RK <1) and SAR (SAR <10 méq/L) show that all sampled groundwater are good qualities for agriculture. According to Wilcox diagram, groundwaters are excellent quality for agriculutre. The osmotic pressure (𝜋 ), the dry residue (RS) and the conductivity values 75% of the sampled waters are excellent quality and 25% average quality for agriculture. Groundwaters from the department of Agboville have a low risk of alkalizing and can be used in irrigation for most crops.